Tensile and Compressive Behavior of Sansevieria Fiber Polyester Starch Composite: Perilaku Tarik dan Tekan Komposit Serat Sansevieria, Poliester, dan Tepung - Garida, Alzan Laga; Tjahjanti, Prantasi Harmi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Composite materials reinforced with natural fibers are increasingly investigated for lightweight engineering applications. Specific Background Sansevieria fiber composites with polyester matrices have shown promising mechanical properties, yet the modification of the matrix using amylum starch remains insufficiently documented. Knowledge Gap Limited studies report how varying amylum starch concentrations alter tensile and compressive responses of alkali-treated Sansevieria fiber composites. Aims This study determines the mechanical characteristics of Sansevieria fiber reinforced polyester composites with 5% NaOH treatment and amylum starch additions of 6–10 wt% through standardized tensile and compressive tests. Results Hand lay-up specimens tested under ASTM D-638 and ASTM D-695 show that starch addition increases tensile strength, with a maximum stress of 35.53 MPa at 8%, while compressive strength decreases, with the highest value of 108.27 MPa observed in specimens without starch. Novelty The work provides direct experimental comparison of dual mechanical behaviors under systematic starch concentration variations in a natural fiber composite system. Implications The findings guide material selection and matrix formulation for applications requiring higher tensile performance while considering compressive limitations. Keywords: Sansevieria Fiber, Polyester Composite, Amylum Starch, Tensile Strength, Compressive Strength Key Findings Highlights Peak tensile stress recorded at eight percent starch addition Compression capacity reduced with matrix modification Alkali treated fibers maintained load transfer during stretching